Medo, morte e música - Rigaud, João-Heitor (Trabalhos de Antropologia e Etnologia, 2020)
Death is an inherent part of the living condition. Therefore, both the unknown that death represents, coupled with the notion of an end, reinforce the natural tendency for the preservation of life as a contribution to the preservation of the species. This implies that fear is a defence mechanism against potential situations of annihilation. Fear, when it does not block action, is an excellent stimulus for the investigation of strategies that aim to resolve potentially destructive problems of individual existence and consequently the personal contribution to the group. In this context, if the recourse to art would have a relevant role, musical sound stands out for its capacity for communication at a distance, transforming fear into joy and isolation into socialisation. Music, being the artistic specialty that is, goes beyond the individual hope of life biologically associated with each living being, and assumes a tactical function as an indispensable element for the production of creative energy. The Alpine para digm is in this aspect fundamental and allows the understanding of the essential aspects of human nature. From fear to joy and from death to life, the pathways, meanings, ambiguities and riches that are contained in existence are qualities that make a living being not simply exist, but to be intensely alive, embracing the totality of the experience of life itself. Vida, a qual não existe sem qualidade.